Skarns and Skarn Deposits - Meinert, Lawrence (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1992)
Summary Skarn deposits occur throughout the world and have been mined for a variety of elements. This paper describes the basic stages of skarn formation and the main causes of variation from the general evolutionary model. Seven major classes of skarn deposits (Fe, W, Au, Cu, Zn, Mo and Sn) are briefly described, and relevant geological and geochemical features of important examples are summarized in a comprehensivetable. The important geochemical and geophysical parameters of skarn deposits arediscussed, followed by a summary of important petrologic and tectonic constraints on skarn formation. Finally, exploration models are presented for several major skarn types,with a plea for field mapping as a fundamental basis for future studies.